Sustainable parking management strategies for public hospitals : a case study of Tengku Ampuan Afzan Hospital, Kuantan and Sultan Haji Ahmad Shah Hospital, Temerloh / Intan Nur Syuhada Mohd Zahari and Ashrof Zainuddin - Mohd Zahari, Intan Nur Syuhada; Zainuddin, Ashrof (2018)
This study was conducted to investigate the efficiency of parking lot management at Tengku Ampuan Afzan Hospital, Kuantan (HTAA) and Sultan Haji Ahmad Shah Hospital, Temerloh. Parking facilities can be considered as a part of planning requirement that can affect the overall traffic management. The lack of parking lots is a serious problem and this causes the percentage of roadside parking to increase especially in and around the hospital area. This study is conduct to identify Sustainable Parking Management Strategies for Public Hospitals. The scope of parking problem is specified to public hospitals in Kuantan and Temerloh. This study adopts the quantitative approach with total respondents of 100 public users including the staffs and visitors of the public hospitals. Then, these data is analysed by using descriptive and ranking analysis. The main objective is to identify the parking guideline for hospital, the second objective is to know the satisfaction of customers towards the parking facilities at hospitals, and the third objective is to identify the strategy for hospital parking space solution. Based on structured surveys and observation, it is hoped that this study can came out with a good result. In concluding this study, the researcher will propose a guideline for sustainable parking management strategy for Tengku Ampuan Afzan Hospital and Sultan Haji Ahmad Shah Hospital for consideration by the relevant authorities such as MPK and the management of Tengku Ampuan Afzan Hospital and Sultan Haji Ahmad Shah Hospital. Numerous strategies were been suggested to overcome or at least to lower the number of parking problem; for example sharing vehicle to the work place and using shuttle bus service.